Strengthening the Mental Health of Elderly Farmers After the COVID-19 Pandemic: Penguatan Kesehatan Mental Petani Lansia Pasca Pandemi COVID-19 - Kurniyawan, Enggal Hadi; Dewi, Erti Ikhtiarini; Wuryaningsih, Emi Wuri; Deviantony, Fitrio; Fitria, Yeni (DEDIKASI SAINTEK Jurnal Pengabdian Masyarakat, 2022)
The elderly with cognitive decline can experience anxiety, restlessness, and social withdrawal, so they need special attention. Elderly farmers need to get family and community support to increase self-efficacy, resilience, and coping mechanisms in order to reduce the stress they experience. Community service activities are carried out to strengthen the mental health of elderly farmers. This health education activity was carried out at the Sukoreno Village Hall, Kalisat District, Jember Regency. Counseling on improving mental health was carried out for 60 minutes using the media of leaflets, x-banners, and banners with the lecture method followed by discussion, questions, and answers. The material presented to elderly farmers was entitled mental health for the elderly, which is a Mental Health Media Kit from the Ministry of Health of the Republic of Indonesia. The community service activity ended with the distribution of groceries to elderly farmers.